Pengaruh Pengetahuan Tentang Zakat Dan Pengetahuan Perpajakan Terhadap Kepatuhan Wajib Pajak - niisa septi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
Indonesia is one of the countries with a majority Muslim population, in Islam requires to carry out zakat for those who have qualified legally off zakah. The existence of zakat regulation regulated in Law No. 23 of 2011 on The Management of zakat that has been paid by taxpayers can be a deduction of taxable income. The research aims to find out if there is a significant influence of knowledge about zakat and taxation knowledge on taxpayer compliance. This research is quantitative research. The sample of this study was taxpayers registered in KPP Yogyakarta using 88 respondents obtained using questionnaires through google form and questionnaires. Data is processed using IBM SPSS software version 2.0. The results of this study showed that 1) knowledge of zakat has no a significant effect on taxpayer compliance, 2) Taxation knowledge has a significant effect on taxpayer compliance.Keywords : knowledge of zakat, knowledge of taxation, tax compliance